2022
DOI: 10.1016/j.artd.2021.11.021
|View full text |Cite
|
Sign up to set email alerts
|

History of COVID-19 Was Not Associated With Length of Stay or In-Hospital Complications After Elective Lower Extremity Joint Replacement

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…One multicenter cohort study of hip fracture patients in the UK found that SARS-CoV-2 positive patients had an increased length of postoperative hospital stay compared to controls (13.8 days vs. 6.7 days, P < 0.001) ( 21 ). These results are somewhat discordant with those of Jungwirth-Weinberger et al ( 22 ), who reported that SARS-CoV-2 was not predictive of post-arthroplasty median length of stay after controlling for confounding variables such as age, sex, and comorbidity index ( 22 ). In a cardiac surgery patient cohort, the average length of postoperative stay for SARS-CoV-2 positive patients was 3 days, compared to 1.8 days in controls ( P = 0.002) ( 23 ).…”
Section: Discussionsupporting
confidence: 76%
“…One multicenter cohort study of hip fracture patients in the UK found that SARS-CoV-2 positive patients had an increased length of postoperative hospital stay compared to controls (13.8 days vs. 6.7 days, P < 0.001) ( 21 ). These results are somewhat discordant with those of Jungwirth-Weinberger et al ( 22 ), who reported that SARS-CoV-2 was not predictive of post-arthroplasty median length of stay after controlling for confounding variables such as age, sex, and comorbidity index ( 22 ). In a cardiac surgery patient cohort, the average length of postoperative stay for SARS-CoV-2 positive patients was 3 days, compared to 1.8 days in controls ( P = 0.002) ( 23 ).…”
Section: Discussionsupporting
confidence: 76%
“…Statistical analyses were performed using SAS 9.4 (SAS Institute Inc., Cary, NC, USA). Using a significance level of 0.05 and a power of 90%, power analysis revealed a 3-hour difference ( 10 ) in hospital LOS would be detected with 462 patients in each cohort. To account for a potentially high dropout rate in the midst of the pandemic, we aimed to increase our patient cohort by over 50%.…”
Section: Methodsmentioning
confidence: 99%
“…Although the population of patients with a previous history of COVID-19 is insufficient to draw definitive conclusions, based on these results, we can say that patients who fully recover from COVID-19 may be good candidates for joint surgery. Similarly to us, a study by Jungwirth-Weinberger et al on the impact of previous COVID-19 infection on the complications of elective arthroplasty reported that previous COVID-19 infection did not lead to an extended hospital stay or more complications at the hospital ( 62 ). Furthermore, the same authors found that patients with a positive history of COVID-19 had a low rate of VTE following arthroplasty ( 63 ).…”
Section: Discussionmentioning
confidence: 65%